A multi-country qualitative evaluation of rapid mortality surveillance during the COVID-19 pandemic - Carlie Congdon; Farnaz Malik; Ruxana Jina; Diana Kumar; Philip W. Setel (PLoS ONE, 2026)
Background Low- and middle-income countries without well-functioning civil registration and vital statistics (CRVS) systems struggle to obtain accurate and complete counts of total (i.e., all-cause) mortality, especially during a pandemic. The aim of this evaluation was to assess whether rapid mortality surveillance (RMS) provided timely and useful counts of deaths to inform pandemic response, despite competing demands on government and public health responders, during the COVID-19 pandemic. This is the first published evaluation of efforts to test the feasibility, utility, and impact of efforts to improve or establish mortality surveillance. Methods We supported 13 low- and middle-income countries to implement RMS during the first wave of the COVID-19 pandemic. From August to October 2021, we conducted a qualitative assessment of each country’s progress. Results Analysis of in-depth interviews with 16 respondents in 13 countries surfaced common themes related to facilitators of RMS implementation. These include 1) government ownership and buy-in; 2) data collection and digitalization; 3) interagency collaboration and data sharing; 4) data analysis and interpretation; and 5) data use for decision-making. Conclusion Robust and digitalized CRVS systems can serve the rapid mortality surveillance function well. For locations where digitalization and connectivity of systems are still improving, more feasible and fit-for-purpose approaches are needed. These findings should inform the development of CRVS mortality surveillance functions in low- and middle-income countries.